Assessing safety and efficacy of TNFi treatment in late onset ankylosing spondylitis: a TURKBIO registry study - Uslu, Sadettin; Gulle, Semih; Sen, Gercek; Cefle, Ayse; Yilmaz, Sema; Kocaer, Sinem Burcu; Onen, Fatos (Nature Portfolio, 2024)
Clinical data on the use of tumour necrosis factor inhibitors (TNFi) in late-onset ankylosing spondylitis (LoAS) are limited. The present study aimed to evaluate efficacy, safety, and treatment adherence associated with the initial use of TNFi therapy in biologic naive patients diagnosed with LoAS. Patients whose age of onset was >= 45 years and < 45 years were classified as having LoAS and YoAS, respectively, based on the age of symptom onset. There were 2573 patients with YoAS and 281 LoAS. Baseline disease activity measures were similar between the groups. No significant differences were seen between the two groups in response to treatment and in remaining on the first TNFi at 6, 12 and 24 months. In the LoAS group, the analysis showed that TNFi discontinuation was linked to VAS pain score (HR 1.04; 95% CI 1.01-1.06). Patient groups had similar rates of adverse events (YoAS: 8.7% vs. LoAS: 11.7%). In both biologic naive LoAS and YoAS patients, the study showed that the initial TNFi therapy was equally effective and safe.
Keywords: Ankylosing spondylitis; Late-onset ankylosing spondylitis; TNFi; 45 years; TURKBIO